KONTAK DAN KONFLIK BAHASA PADA REMAJA MINORITAS DESA DENANYAR: KAJIAN SOSIOLINGUISTIK - Zidny Kamilatal Aqliyyah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Language contact and language conflict are sociolinguistic studies that are important to be studied further. Each community has different language characteristics, such as language contact and language conflict among minority teenagers in Denanyar village. The purpose of this study is to describe language contact and conflict in adolescents who continue their education in Denanyar village using qualitative descriptive research. Data collection techniques were taken based on the results of observations, observations, and interviews. Sources of data were taken from three teenagers belonging to the minority from a group of teenagers who came from the village of Denanyar. The results of this study confirm the existence of language contact and language conflict in Denanyar village through the phenomenon of language contact and language conflict in the dormitory environment for students from Java (Denanyar village) with students from Batam, the phenomenon of language contact and language conflict in the school environment for students from Java (Denanyar village) with students from Madura, and the phenomenon of language contact and language conflict in the school environment for students from Java (Denanyar village) with students from Solo.Keywords: language, contact, conflict. Keywords: language, contact, conflict